Switching characterization of cascaded multilevel-inverter-controlled systems - Gupta, R.; Ghosh, Arindam; joshi, A. (Institute of Electrical and Electronic Engineers, 2008)
In this paper, the method of triangular carrier switching control of two-level inverters is extended to cascaded multilevel inverters using phase-shifted multicarrier unipolar pulsewidth modulation (PWM). The condition for smooth modulation is obtained using the Bessel’s function representation ofthe PWM output and the switching condition of the multilevelinverter-controlled system. A method is proposed for the determination of the minimum amplitude of the triangular carrier for smooth modulation at fixed switching frequency. It is shown that the multilevel modulation based on the phase-shifted carriers significantly reduces the ripple magnitude in the switching function and allows the use of a smaller carrier amplitude under closed loop. This increases the forward gain and, hence, improvesthe tracking characteristics. The proposed cascaded multilevel inverter control is implemented for the operation of a distribution static compensator (DSTATCOM) in the voltage control mode. The xperimental verification of the theoretical and simulation results is provided through a field-programmable gate array (FPGA) based control of a laboratory model of a single-phase DSTATCOM.